Best Practices – Promising Initiatives at TCS - Tipnis, Sujata; Das, Banalata (Qualitative and Quantitative Methods in Libraries; Vol 7 No 2 (2018): June 2018 Issue, 2019)
Best practices are implemented for better performance of the organisation - they improve productivity, increase efficiency of operations and also help in optimization of resources. They are generally accepted as superior to any alternative. The use of Information Communication Technology (ICT) and digitization have changed the organizational culture of libraries. New well defined, user focused best practices using ICT in the library field are being initiated to ensure success. This paper describes some of the best practices followed at Information Resource Centre (IRC), Tata Consultancy Services (TCS), a global leader in IT services. Paper discusses importance and benefits of introducing best practices such as Internal Audit, Webex Review Meet, Pop up library and Book for Book at TCS IRCs. These are the processes that are being implemented to improve IRC’s processes, activities; optimization and deliver value add services to its users.